High-capacity lithium iron manganese phosphate positive electrode material and preparation method thereof and lithium battery
By doping nickel into the lithium manganese iron phosphate positive electrode material and using hydrothermal method with carbon source and TiCN coating technology, the problem of degradation of the material in high energy density applications is solved, and higher structural stability and electrochemical performance are achieved.
Patent Information
- Application Number
- CN202411897046.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-23
AI Technical Summary
The iron manganese lithium phosphate cathode material cannot meet the demand for high energy density in the rapidly developing electric vehicle applications, and the dissolution of metal elements destroys the crystal structure, resulting in a decline in overall performance.
The precursor is prepared by doping nickel into the core of lithium manganese iron phosphate, combining with hydrothermal method, and coated with carbon source and TiCN thereon to form a high-capacity lithium manganese iron phosphate positive electrode material.
It improves the structural stability of the material, suppresses lattice defects and ginger Taylor effect, and improves charge and discharge performance, rate performance and cycle stability.
Smart Images

Figure CN119370823B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium manganese iron phosphate positive electrode materials, in particular to a high-capacity lithium manganese iron phosphate positive electrode material and a preparation method thereof and a lithium battery. Background Art
[0002] With the development of economy, people require energy storage devices to have longer cycle life and higher electrochemical performance, be safer, and have cheaper materials. Lithium iron manganese phosphate is a very popular positive electrode material with good safety and stability. Carbon coating, hypervalent doping, nanocrystallization and other methods can improve the performance of Li + Poor diffusion and conductivity lead to low rate performance. However, lithium iron manganese phosphate cathode materials are gradually unable to meet the high energy density requirements of lithium-ion batteries for the rapid development of electric vehicles.
[0003] Lithium iron manganese phosphate cathode material has good safety and thermal stability, and higher energy storage density and longer cycle life will become advantages in future market competition. However, in practical applications, the problem of metal element dissolution and destruction of crystal structure leads to a serious decline in its comprehensive performance. Therefore, it is necessary to modify the lithium iron manganese phosphate cathode material. Summary of the invention
[0004] The present invention overcomes the above technical problems and provides a high-capacity lithium iron manganese phosphate positive electrode material and a preparation method thereof and a lithium battery. The high-capacity lithium iron manganese phosphate positive electrode material prepared by the present invention has excellent discharge performance and cycle performance.
[0005] The present invention solves the above technical problems through the following technical solutions.
[0006] The present invention discloses a method for preparing a high-capacity lithium manganese iron phosphate positive electrode material, which is characterized by comprising the following steps:
[0007] S1. The precursor solution is heated at 150-170°C for 7-10h, solid-liquid separation, centrifugation, and drying to obtain a precursor;
[0008] The precursor solution includes a lithium hydroxide solution, a salt solution and a modified phosphoric acid solution;
[0009] The raw materials for preparing the salt solution include manganese sulfate, ferrous sulfate and nickel acetate;
[0010] The raw materials for preparing the modified phosphoric acid solution include concentrated phosphoric acid and ATMP;
[0011] Among them, ATMP is aminotrimethylenephosphonic acid (CAS No.: 6419-19-8), and its structural formula is ;
[0012] S2. Wet-grinding the precursor, the carbon source and TiCN to obtain a slurry;
[0013] S3. The slurry is sintered at 650-750°C for 8-12 hours to obtain a high-capacity lithium manganese iron phosphate positive electrode material.
[0014] In S1, the concentration of the lithium hydroxide solution is 0.8~1 mol / L.
[0015] In S1, the concentration of manganese sulfate in the salt solution is 0.4-0.5 mol / L.
[0016] In S1, the solvents of the lithium hydroxide solution and the salt solution are both water.
[0017] In S1, manganese sulfate, ferrous sulfate and nickel acetate in the salt solution are mixed in a molar ratio of Mn:Fe:Ni=0.6:0.4-x:x, where x=0.02-0.05.
[0018] In S1, the raw materials for preparing the modified phosphoric acid solution include concentrated phosphoric acid, ATMP and polyethylene glycol.
[0019] Furthermore, in S1, the polyethylene glycol is PEG200 or PEG400.
[0020] In S1, the modified phosphoric acid solution contains polyethylene glycol: concentrated phosphoric acid: ATMP = 100 mL: 2.5-3 mL: 0.6-0.8 mg. ATMP is added as a phosphorus source and a structure-directing agent. The chelation effect of ATMP can be used for structural guidance of the synthesis of lithium manganese iron phosphate, so that the lithium manganese iron phosphate particles are evenly distributed, and the pores between the particles can help increase the contact area between the nanoparticles and the electrolyte, effectively improving the diffusion efficiency of lithium electrons.
[0021] In S1, ascorbic acid is further added to the salt solution, and the molar ratio of manganese sulfate to ascorbic acid in the salt solution is 10:1-5.
[0022] In S1, the preparation process of the precursor solution is to add lithium hydroxide solution to modified phosphoric acid solution so that the pH value is 10.0-11.5; and then add salt solution so that the pH value of the precursor solution is 6.5-7.5.
[0023] In S2, the carbon source is glucose or sucrose.
[0024] In S2, the mass ratio of the precursor: carbon source: TiCN is 100: (2-5): (0.5-1.5), preferably 100: (3.0-4.5): (0.6-1.0). TiCN exists at the grain boundary of the lithium manganese iron phosphate positive electrode material as a nucleation site and steric inhibitor, which can prevent excessive expansion of the grain boundary and grain growth, and is beneficial to obtain a nano-scale positive electrode material.
[0025] In S1, the drying method is vacuum drying using a vacuum drying oven.
[0026] In S1, the drying temperature is 150-175° C., and the drying time is 5-10 h.
[0027] In S3, the heating rate before sintering is 3-6°C / min.
[0028] In S3, the sintering needs to be performed under the protection of an inert gas atmosphere.
[0029] In S3, after the sintering, the product needs to be naturally cooled to room temperature under the protection of an inert gas, and the room temperature is 20-25°C.
[0030] In S2, the wet grinding medium is water and ethanol; preferably, the mass ratio of water to ethanol is 1:2-3.
[0031] In S2, the ball-to-material ratio of the wet grinding is 5:1.
[0032] In S2, the stirring speed of the wet grinding is 400-500 rpm.
[0033] In S2, the wet grinding time is 4.5 to 6.5 hours.
[0034] In S2, the solid content of the slurry is 55-60%.
[0035] The high-capacity lithium iron manganese phosphate positive electrode material prepared by the above-mentioned method for preparing the high-capacity lithium iron manganese phosphate positive electrode material comprises a core and a coating layer;
[0036] The molecular formula of the core structure is LiMn 0.6 Fe 0.4-x Ni x PO 4 , x=0.02~0.05;
[0037] The raw materials of the coating layer include a carbon source and TiCN.
[0038] The raw materials of the coating layer are carbon source and TiCN.
[0039] A lithium battery comprises the aforementioned high-capacity lithium iron manganese phosphate positive electrode material.
[0040] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0041] Compared with the prior art, the present invention has the following beneficial effects:
[0042] 1. The high-capacity lithium iron manganese phosphate positive electrode material of the present invention strengthens the PO bond by doping nickel (Ni) in the lithium iron manganese phosphate core, thereby improving the structural stability of the material. This structural improvement helps to suppress lattice defects and the Jan-Taylor effect, thereby improving the charge and discharge performance, rate performance and cycle stability of the material. Although nickel doping may increase certain costs, compared with high-nickel ternary batteries, this doped lithium iron manganese phosphate battery still has obvious advantages in price.
[0043] 2. The present invention adopts a hydrothermal method to prepare a precursor, and then coats the precursor with a carbon source and TiCN to obtain a high-capacity lithium iron manganese phosphate positive electrode material. The addition of a small amount of TiCN not only serves as a nucleation site, but also as a steric inhibitor, which exists in the grain boundaries of the lithium iron manganese phosphate positive electrode material, and can prevent excessive expansion of the grain boundaries and growth of grains, which is beneficial for the preparation of nano-scale positive electrode materials.
[0044] 3. The high-capacity lithium manganese iron phosphate positive electrode material prepared by the present invention has a discharge specific capacity of 153~158 mAh / g at 1.0C, and in some preferred embodiments, it is 153.6~157.6 mAh / g; the discharge specific capacity at 2.0C is 149~153 mAh / g, and in some preferred embodiments, it is 149.2~152.7 mAh / g; the discharge specific capacity at 5.0C is 135~138 mAh / g, and in some preferred embodiments, it is 135.3~137.2 mAh / g. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 This is the SEM image of the high-capacity lithium manganese iron phosphate positive electrode material prepared in Example 1.
[0046] Figure 2 This is the SEM image of the high-capacity lithium manganese iron phosphate positive electrode material prepared in Comparative Example 1.
[0047] Figure 3 This is the SEM image of the high-capacity lithium manganese iron phosphate positive electrode material prepared in Comparative Example 2. DETAILED DESCRIPTION
[0048] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and carefully in combination with preferred embodiments below, but the protection scope of the present invention is not limited to the following specific embodiments.
[0049] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0050] The "range" disclosed in the present invention is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of a particular range. The range defined in this way can be inclusive or exclusive of end values, and can be combined arbitrarily, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60-120 and 80-110 is listed for a specific parameter, it is understood that the range of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following ranges can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present invention, unless otherwise specified, the numerical range "ab" represents an abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" represents that all real numbers between "0-5" have been fully listed herein, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0051] If not otherwise specified, all embodiments and optional embodiments of the present invention can be combined with each other to form a new technical solution.
[0052] Unless otherwise specified, all technical features and optional technical features of the present invention can be combined with each other to form a new technical solution.
[0053] If not otherwise specified, all steps of the present invention may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0054] If there is no special explanation, the "include" and "comprising" mentioned in the present invention represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0055] If not specifically stated, in the present invention, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0056] Example 1
[0057] 1. High-capacity lithium manganese iron phosphate positive electrode material of this embodiment:
[0058] The core is LiMn 0.6 Fe 0.37 Ni 0.03 PO 4 ;
[0059] The raw materials for preparing the coating layer are glucose and TiCN.
[0060] 2. Preparation method of high-capacity lithium manganese iron phosphate positive electrode material in this embodiment:
[0061] (1) Raw material preparation:
[0062] The lithium hydroxide solution is a 1 mol / L lithium hydroxide aqueous solution;
[0063] The concentration of manganese sulfate in the salt solution is 0.5 mol / L, and manganese sulfate, ferrous sulfate and nickel acetate are mixed in a molar ratio of Mn:Fe:Ni:ascorbic acid = 60:37:3:6;
[0064] In the modified phosphoric acid solution, polyethylene glycol (PEG400): concentrated phosphoric acid: ATMP = 100 mL: 2.5 mL: 0.6 mg.
[0065] (2) Add lithium hydroxide solution to the modified phosphoric acid solution to make the pH value 11; then add salt solution to make the pH value of the precursor solution 7.5.
[0066] (3) The precursor solution was heated at 160°C for 8 h in a hydrothermal reactor, solid-liquid separated, centrifuged, and vacuum dried at 150°C for 8 h to obtain a precursor;
[0067] (4) wet-grinding the precursor, carbon source (glucose) and TiCN to obtain a slurry;
[0068] In this embodiment, the mass ratio of precursor, carbon source and TiCN is 100:3.5:0.83;
[0069] In this embodiment, the wet grinding medium is water and ethanol (water: ethanol = 3:1), the ball-to-material ratio of the wet grinding is 5:1, and the wet grinding is carried out at a rotation speed of 450 rpm for 6 hours to prepare a slurry with a solid content of 55%.
[0070] (5) The sintering process needs to be carried out under nitrogen protection. The heating rate before sintering is 3°C / min. The slurry is heated to 680°C and sintered for 12 hours. After sintering, it is still naturally cooled to room temperature (20°C) in a nitrogen atmosphere. The SEM image of the obtained high-capacity lithium manganese iron phosphate positive electrode material is shown in Figure 1 .
[0071] Example 2
[0072] The difference between this embodiment and embodiment 1 is that:
[0073] Polyethylene glycol in modified phosphoric acid solution: concentrated phosphoric acid: ATMP = 100 mL: 3.0 mL: 0.6 mg.
[0074] Example 3
[0075] The difference between this embodiment and embodiment 1 is:
[0076] Polyethylene glycol in modified phosphoric acid solution: concentrated phosphoric acid: ATMP = 100 mL: 2.5 mL: 0.7 mg.
[0077] Example 4
[0078] The difference between this embodiment and embodiment 1 is:
[0079] Heat in a hydrothermal reactor at 170 °C for 8 h.
[0080] Example 5
[0081] The difference between this embodiment and embodiment 1 is:
[0082] The mass ratio of precursor, carbon source and TiCN is 100:3.5:0.8.
[0083] Example 6
[0084] The difference between this embodiment and embodiment 1 is:
[0085] The mass ratio of precursor, carbon source and TiCN is 100:4.5:0.7.
[0086] Comparative Example 1
[0087] The difference between this comparative example and Example 1 is:
[0088] Polyethylene glycol in modified phosphoric acid solution: concentrated phosphoric acid: ATMP = 100 mL: 2.5 mL: 1.2 mg. The SEM image of the obtained high-capacity lithium manganese iron phosphate positive electrode material is shown in Figure 2 .
[0089] Comparative Example 2
[0090] The difference between this comparative example and Example 1 is:
[0091] The modified phosphoric acid solution contains polyethylene glycol: concentrated phosphoric acid = 100 mL: 3.0 mL. The modified phosphoric acid solution does not contain ATMP. The SEM image of the obtained high-capacity lithium manganese iron phosphate cathode material is shown in Figure 3 .
[0092] Comparative Example 3
[0093] The difference between this comparative example and Example 1 is:
[0094] S3 was heated in a hydrothermal reactor at 160°C for 12 h.
[0095] Comparative Example 4
[0096] The difference between this comparative example and Example 1 is:
[0097] The mass ratio of the precursor to the carbon source is 100:5, and this embodiment does not contain TiCN.
[0098] Test Case
[0099] The positive electrode materials prepared in the above examples and comparative examples are prepared into button-type half-cells, and the preparation steps are as follows:
[0100] (1) Adding a solvent of N-methylpyrrolidone (NMP) to a high-capacity lithium manganese iron phosphate positive electrode material: acetylene black: polyvinylidene fluoride in a mass ratio of 8:1:1 to adjust the viscosity to 4000-8000 mPa·s to prepare a positive electrode slurry;
[0101] (2) The positive electrode slurry is evenly coated on one surface (perpendicular to the thickness direction) of the aluminum foil (positive electrode current collector) and dried, and then rolled and sheared to obtain a positive electrode sheet containing a positive electrode film layer.
[0102] (3) Using lithium hexafluorophosphate-ethyl methyl carbonate as the electrolyte and polypropylene as the isolation membrane, the prepared positive electrode sheet and negative lithium sheet are combined to make a button half-cell.
[0103] The button half-cell was tested for discharge capacity at 1.0C, 2.0C and 5.0C (measured at 20°C) in the voltage range of 2.0V~3.8V using a Blue Electric device. The test results are shown in Table 1 below.
[0104]
[0105] The above embodiments and comparative examples are combined with Table 1 to show that:
[0106] In Comparative Example 1, too high an ATMP content would cause particle aggregation and fail to form uniformly dispersed particles.
[0107] In Comparative Example 2, the absence of ATMP resulted in irregular growth of the surface of the positive electrode material grains and a relatively rough surface.
[0108] In Comparative Example 3, too long a heating time causes the precursor crystal growth to dominate and the nucleation process to become secondary, which results in the primary particles being too large, the sphericity being deteriorated, and the gaps between the materials increasing.
[0109] In Comparative Example 4, since the addition of ATMP to the modified concentrated phosphoric acid solution can promote the growth of lithium iron manganese phosphate, if TiCN is not added during the next sintering, the grains will be larger, and the positive electrode material without TiCN has poor cycle stability.
[0110] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods. The specific embodiments described above further describe the purpose, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a high-capacity lithium manganese iron phosphate positive electrode material, characterized in that: The following steps are involved: S1. The precursor solution is heated at 150-170°C for 7-10h, solid-liquid separation, centrifugation, and drying to obtain a precursor; S2. Wet-grinding the precursor, the carbon source and TiCN to obtain a slurry; S3. The slurry is sintered at 650-750°C for 8-12h to obtain a high-capacity lithium manganese iron phosphate positive electrode material; The precursor solution includes a lithium hydroxide solution, a salt solution and a modified phosphoric acid solution; The raw materials for preparing the salt solution include manganese sulfate, ferrous sulfate and nickel acetate; The raw materials for preparing the modified phosphoric acid solution include polyethylene glycol, concentrated phosphoric acid and ATMP; wherein ATMP is aminotrimethylenephosphonic acid; The manganese sulfate, ferrous sulfate and nickel acetate in the salt solution are mixed in a molar ratio of Mn:Fe:Ni = 0.6:0.4-x:x, where x = 0.02-0.05; The high-capacity lithium manganese iron phosphate positive electrode material comprises a core and a coating layer; The molecular formula of the core structure is LiMn 0.6 Fe 0.4-x Ni x PO4, x = 0.02 ~ 0.05; The raw materials of the coating layer include a carbon source and TiCN; The modified phosphoric acid solution contains polyethylene glycol: concentrated phosphoric acid: ATMP = 100 mL: 2.5-3 mL: 0.6-0.8 mg.
2. The method for preparing a high-capacity lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: Meet at least one of the following conditions ①~②: ① The lithium hydroxide concentration in the lithium hydroxide is 0.8-1 mol / L; ② The concentration of manganese sulfate in the salt solution is 0.4-0.5 mol / L.
3. The method for preparing a high-capacity lithium iron manganese phosphate positive electrode material according to claim 2, characterized in that: The preparation process of the precursor solution is to add lithium hydroxide solution to modified phosphoric acid solution to make the pH value be 10.0-11.5; and then add salt solution to make the pH value of the precursor solution be 6.5-7.
5.
4. The method for preparing a high-capacity lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The carbon source is glucose or sucrose.
5. The method for preparing a high-capacity lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The mass ratio of the precursor: carbon source: TiCN is 100:2~5:0.5~1.
5.
6. The method for preparing a high-capacity lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: Meet at least one of the following conditions ①~②: ① The drying method is vacuum drying; ② The drying temperature is 150-175°C, and the drying time is 5-10 hours.
7. The method for preparing a high-capacity lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: Meet at least one of the following conditions ①~③: ① The heating rate before sintering is 3~6℃ / min; ② The sintering is carried out under the protection of an inert gas atmosphere; ③ After the sintering, the product is naturally cooled to room temperature under the protection of an inert gas.
8. The method for preparing a high-capacity lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: Meet at least one of the following conditions ①~④: ① The wet grinding medium is water and ethanol; ② The stirring speed of the wet grinding is 400-500 rpm; ③ The wet grinding time is 4.5~6.5h; ④The solid content of the slurry is 55-60%.
9. A high-capacity lithium iron manganese phosphate positive electrode material prepared by the method for preparing a high-capacity lithium iron manganese phosphate positive electrode material according to any one of claims 1 to 8.
10. A lithium battery, characterized in that: Comprising the high-capacity lithium iron manganese phosphate positive electrode material as described in claim 9.
Citation Information
Patent Citations
Preparation method of monodisperse nanometer olivine type manganese-based phosphate positive-pole material and lithium-ion secondary battery thereof
CN102810664A
Lithium manganese iron phosphate material and preparation method thereof, positive pole piece and lithium ion battery
CN117525331A
Composite cathode active material, cathode and lithium battery that include the composite cathode active material, and method of preparing the composite cathode active material
US20130112915A1